Maximizing Firm Value: Analyzing Profitability and Leverage with Tax Avoidance Interventions - Endah Susilowati; Aidha Kurnia Wardhani Fadilah; Sofie Yunida Putri; Sari Andayani; Nanda Wahyu Indah Kirana (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2024)
This study aims to analyze whether there is an effect between Profitability, Leverage, and tax avoidance toward firm value, either directly or indirectly. This research uses quantitative methods with partial least square analysis techniques. The data was obtained through the official website of the Indonesia Stock Exchange. This study found that 58 manufacturing companies were listed on the Indonesia Stock Exchange from 2016–to 2018. The results indicate that profitability and leverage do not affect tax avoidance and profitability. Leverage affects firm value, and tax avoidance does not mediate the effect of Profitability and Leverage toward firm value. Tax avoidance does not mediate the impact of leverage on firm value because the higher the leverage, the greater the funds provided by the creditor, and this makes investors careful about investing in companies with a high leverage ratio. This study implies that maximizing firm value does not necessarily require the company to engage in tax avoidance schemes since increasing profit will signal to the investor that the company has been managed effectively and ultimately maximizes firm value.